L4/L5 disc herniation in a 13-year-old boy - Domínguez-Gasca, Luis G. (2021)
Background. Low back pain in children and adolescents is relatively frequent, however, lumbar disc herniation is rare, lesser of 2,500 cases have been reported in the literature since 1945. Clinical case: A 13 years old male with lumbar pain with associated to L5 left radicular pain, his symptomatology initiated immediate after direct trauma during sports practice, magnetic resonance study showed disc herniation L4 / L5, adding paresis of muscles innervated by L5 root, so discoidectomy was performed, derived to rehabilitation with muscle strength recovery of involved muscles. Conclusions: Lumbar disc herniation in children and adolescents is rare, is associated with trauma in 2/3 of the cases, the study of choice is magnetic resonance; conservative treatment is effective for patients in these stages of life; surgical treatment is indicated due to a poor response of the conservator management.